Characterization of a Novel Bacteriophage swi2 Harboring Two Lysins Can Naturally Lyse Escherichia coli - Sui, Bingrui; Qi, Xin; Wang, Xiaoxue; Ren, Huiying; Liu, Wenhua; Zhang, Can (Frontiers in Microbiology, 2021)
The novel virulent Siphoviridae bacteriophage swi2 was isolated from a pig farm, and its biological characteristics, genome architecture, and infection-related properties were characterized. Phage swi2 has a high titer of 1.01×1012 PFU/mL with good tolerance to UV rays and remains stable in the pH range of 6 10 and at temperatures less than 50°C. One-step growth analysis revealed that phage swi2 had a 25 min latent period with a large burst size (1000 PFU/cell). The biological characteristics indicated that swi2 had good host infectivity and effective lytic activities. The genome of phage swi2 is composed of 47611 bp with a G+C content of 46.50%. Eighty-nine orfs were predicted, and only 18 of them have known functions. No virulence genes or drug resistance genes were found in the genome. Genome sequence comparison of phage swi2 showed that there were a total of 10 homologous phages in the database with low similarity (less than 92.51% nucleotide identity and 66% query coverage). The predicted host lysis-related genes of phage swi2 consist of one holin, two endolysins, and Rz/Rz1 equivalents. Antibacterial activity assays showed that both endolysins could naturally reduce the host Escherichia coli 51 titers by 1 log unit both in vitro and in vivo, EDTA showed no obvious synergistic action, and holin had no lytic effects on the host cell. These results provide necessary information for the development of antibiotic alternatives for the treatment of multidrug-resistant Escherichia coli infection.